Sucking salt Caribbean women writers, migration, and survival - Gadsby, Meredith (University of Missouri Press, 2006)
"Examines the literature of black Caribbean emigrant and island women including Dorothea Smartt, Edwidge Danticat, Paule Marshall, and others, who use the terminology and imagery of "sucking salt" as an articulation of a New World voice connoting adaptation, improvisation, and creativity, offering a new understanding of diaspora, literature, and feminism"--Provided by publisher.